Gingival cyst of new born: a case report - Madathil, Jinisha; Negi, Bhupender Singh; Kumar, Nileena R. (International Journal of Contemporary Pediatrics, 2016)
Dental lamina cyst, also known as gingival cyst of new born, is a benign oral mucosal lesion of transient nature. They are often mistaken as natal teeth if present in the lower anterior region. These lesions are usually multiple but do not increase in size. Lesions are self-limiting and spontaneously shed a few weeks or months after birth. Clinical diagnosis of these conditions is important in order to avoid unnecessary therapeutic procedure and provide suitable information to parents about the nature of the lesion.